Determining finite difference weights for the acoustic wave equation by a new dispersion‐relationship‐preserving method. (2nd October 2014) - Liang, Wenquan; Wang, Yanfei; Yang, Changchun
ABSTRACT Numerical simulation of the acoustic wave equation is widely used to theoretically synthesize seismograms and constitutes the basis of reverse‐time migration. With finite‐difference methods, the discretization of temporal and spatial derivatives in wave equations introduces numerical grid dispersion. To reduce the grid dispersion effect, we propose to satisfy the dispersion relation for a number of uniformly distributed wavenumber points within a wavenumber range with the upper limit determined by the maximum source frequency, the grid spacing and the wave velocity. This new dispersion‐relationship‐preserving method relatively uniformly reduces the numerical dispersion over a large‐frequency range. Dispersion analysis and seismic numerical simulations demonstrate the effectiveness of the proposed method.